After image an exploratory study on the effects of hazard and dangerous coverage on Filipino photojournalists Adrian Kenneth Gutlay ; Maria Cristina I. Rara, adviser. - Gutlay, Adrian Kenneth; Rara, Maria Cristina I. (2018)
This thesis is an exploratory study that looks into the effects of the exposure of Filipino journalists to danger and hazard. More importantly, it defines and outlines the current state of existing support systems in place by various news agencies in the Philippines. The study discovered that, while it varies from agency to agency, there is much room for improvement in considering the welfare of the photojournalists especially after difficult or risky assignments. Moreover, only photojournalists who are classified as regular employees are given support, debriefing and equipment in varying levels of adequacy. New employees, or "correspondents" as they are called in most cases, lack benefits given to regular employees. However, as the case varies per agency, both generally have to seek professional help and to provide protective gear and related equipment on their own and at their discretion. Moreover, freelancers have the least level of support. Given the equal importance of the physical safety of the photojournalists with their emotional, social and psychological welfare, and the inevitability of exposure to danger in the regular course of the profession, this study recommends an adequate baseline support system in the profession to address these issues."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: Photojournalists -- Philippines; Photojournalists, Filipino